Individual differences in distinct components of attention are linked to anatomical variations in distinct white matter tracts - Niogi, Sumit N.; Mukherjee, Pratik; Ghajar, Jamshid; McCandliss, Bruce D. (Frontiers in Neuroanatomy, 2010)
Inter-subject variations in white matter tract properties are known to correlate with individual differences in performance in cognitive domains such as attention. The specificity of such linkages, however, is largely unexplored at the level of specific component operations of attention associated with distinct anatomical networks. This study examines individual performance variation within three functional components of attention – alerting, orienting, and conflict processing – identified by the Attention Network Task (ANT), and relates each to inter-subject variation in a distinct set of white matter tract regions. Diffusion tensor imaging data collected at 3T was used to calculate average fractional anisotropy within a set of individualized a priori defined regions of interest using the Reproducible Objective Quantification Scheme (ROQS) (Niogi and McCandliss, 2006; Niogi et al., 2007). Results demonstrate three functionally distinct components of attention that each correlate distinctly with three white matter tract regions. Structure–function correlations were found between alerting and the anterior limb of the internal capsule, orienting and the splenium of the corpus callosum, and conflict and the anterior corona radiata. A multiple regression/dissociation analysis demonstrated a triple dissociation between these three structure-function relationships that provided evidence of three anatomically and functionally separable networks. These results extend previous findings from functional imaging and lesion studies that suggest these three components of attention are subserved by dissociable networks, and suggest that variations in white matter tract microstructure may modulate the efficiency of these cognitive processes in highly specific ways.